The Determinants of the Medical Tourism Supply Chain of Thailand - Ratchada Fongtanakit; Sudawan Somjai; Amnaj Prasitdumrong; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The present study emphasized the integration of medical tourism supply chain   practices among organizations, its antecedents as well as consequences in the medical tourism industry. The study has used the survey-based methodology and employed SEM-PLS as a statistical tool to answer the research questions raised in the study. The findings of this study confirmed the significance of mutual dependency in medical tourism supply chain, and also reported that there is lack of commitment as well as trust within the medical tourism supply chain   members’, which has not identified completely in earlier researches. In the meantime, medical tourism supply chain   information sharing, and coordination also found to be the significant contributory factors in improving the performance of organization. However, certain level of integration and collaboration is still missing in medical tourism supply chain, due to certain deficiencies. Thus, medical tourism is an important sector and business for the tourism industry in Thailand, which needs to enhance SC operations to outperform its competitors and for achieving competitive advantage. The study provides guideline to researchers, policymakers and researchers and argues that the drivers of medical tourism supply chain i.e. mutual dependency, commitment and trust must be focused as those organizational areas which require more efforts to enhance medical tourism supply chain relationships.